Inequality and the State: Comparing U.S. and German Preferences - Giacomo Corneo (Center for Economic Studies and ifo Institute (CESifo), 2000)
Survey data from the United States, West Germany and East Germany are analyzed to compare individual attitudes towards political redistribution in each country. In West Germany the homo oeconomicus effect, the social rivalry effect and the public values effect simultaneously retain an independent explanatory power of individual attitudes. In the United States the third effect disappears. In East Germany both the second and the third effect disappear.
Keywords: 330; Governmental redistribution; political preferences; social rivalry